2020
DOI: 10.1038/s41467-020-18207-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomes of pancreatic preinvasive lesions and cancer reveal acinar metaplastic cells’ heterogeneity

Abstract: Acinar metaplasia is an initial step in a series of events that can lead to pancreatic cancer. Here we perform single-cell RNA-sequencing of mouse pancreas during the progression from preinvasive stages to tumor formation. Using a reporter gene, we identify metaplastic cells that originated from acinar cells and express two transcription factors, Onecut2 and Foxq1. Further analyses of metaplastic acinar cell heterogeneity define six acinar metaplastic cell types and states, including stomach-specific cell type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
172
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(183 citation statements)
references
References 85 publications
11
172
0
Order By: Relevance
“…We used co-immunofluorescence (Co-IF) for EYFP and cell type markers in normal and injured CERTY pancreata to confirm marker expression and to validate transcriptomically-identified populations. In uninjured, tamoxifen-treated CERTY pancreata, EYFP expression is restricted to acinar cells (amylase+) and is absent from ductal (pan-cytokeratin) and islet cells (CHGA+), consistent with prior reports (Figure 2A-B) 13,16 . Under conditions of chronic injury, however, EYFP is expressed in both acinar and ductal cells (including tuft cells) as well as a large population of CHGA+ cells consistent with EEC formation (Figure 2A-B).…”
Section: Lineage Tracing and Scrna-seq Identifies Epithelial Heterogesupporting
confidence: 90%
“…We used co-immunofluorescence (Co-IF) for EYFP and cell type markers in normal and injured CERTY pancreata to confirm marker expression and to validate transcriptomically-identified populations. In uninjured, tamoxifen-treated CERTY pancreata, EYFP expression is restricted to acinar cells (amylase+) and is absent from ductal (pan-cytokeratin) and islet cells (CHGA+), consistent with prior reports (Figure 2A-B) 13,16 . Under conditions of chronic injury, however, EYFP is expressed in both acinar and ductal cells (including tuft cells) as well as a large population of CHGA+ cells consistent with EEC formation (Figure 2A-B).…”
Section: Lineage Tracing and Scrna-seq Identifies Epithelial Heterogesupporting
confidence: 90%
“…To investigate the molecular effects of hyperinsulinemia in the context of PDAC initiation in an unbiased and cell type-specific manner, we undertook scRNAseq. Only a few studies have successfully conducted scRNAseq in the pancreas to date for studying pancreatic cancer (41)(42)(43).…”
Section: Single-cell Transcriptomics Reveals Effects Of Hyperinsulinementioning
confidence: 99%
“…Consistent with previous work, 26 however, we found that senescence markers did not fully overlap at the individual cell level, with a somewhat different distribution of expression of Cdkn2a and Ptgs2 observed in the scRNA-Seq analysis, suggesting that the Cox2 + cells are a subset among several types of non-dividing cell states within lesions. 33 The Ptf1a-CreER model, in which oncogenic Kras is activated in acinar cells, provides rapid PanIN formation in the absence of external induction of inflammation. In this model, we found that pharmacologic inhibition of Cox2 through sulindac, a nonsteroid anti-inflammatory drug, dramatically inhibited PanIN growth, suggesting that the Cox2 + cells provide the major protumourigenic inflammatory drive, essential for disease development.…”
Section: Discussionmentioning
confidence: 99%